GERAKAN REMAJA PEDULI HIV: MEMBANGUN EMPATI MELALUI PAMERAN PHOTOVOICE VIRTUAL - Kamila, Ami (Indonesian Community Service and Empowerment Journal (IComSE), 2024)
The community service program titled "Youth Movement for HIV Awareness: Building Empathy Through Virtual Photovoice Exhibitions" aimed to increase knowledge and reduce stigma towards People Living with HIV/AIDS (PLHIV) among teenagers. Through a participatory educational approach, this program utilized Photovoice media to convey the realities of PLHIV's lives and evoke empathy in participants. A total of 169 respondents from several schools participated in this activity. The pretest and posttest results showed a significant increase in participants' knowledge and inclusive attitudes, with a decrease in the "Less Inclusive" category and an increase in the "Inclusive" category. Evaluation using the Wilcoxon test indicated a significant change in participants' level of inclusivity (p=0.000). This program was also supported by LPPM Unisa Bandung, KPA, and the Bandung Barat District Health Office. In conclusion, Photovoice was effective in changing teenagers' perceptions of HIV, building empathy, and encouraging them to become agents of change. Recommendations for future activities include expanding the program's reach and forming youth cadres for HIV awareness as peer educators.